Deciduous Dental Pulp Stem Cells for Maxillary Alveolar Reconstruction in Cleft Lip and Palate Patients - Daniela Y. S. Tanikawa; Carla C. G. Pinheiro; Maria Cristina A. Almeida; Claudia R. G. C. M. Oliveira; Renata de Almeida Coudry; Diógenes Laercio Rocha; Daniela Franco Bueno (Hindawi Limited, 2020)
Background. To reduce morbidity to cleft patients, new approaches have been developed and here, we report for the first time the use of deciduous dental pulp stem cells (DDPSC) associated with a hydroxyapatite-collagen sponge (Bio-Oss Collagen® 250 mg, Geistlich) for closing alveolar defects during secondary dental eruption, further comparing these results to historical controls. Methods. Six patients, aged 8 to 12, were selected. Autologous DDPSC were isolated from each patient, then associated with the biomaterial and this bone tissue engineered set was used to fill the alveolar defect. Computed tomography was performed to assess both preoperative and 6- and 12-month postoperative outcomes. Overall morbidity was recorded. Historical controls consisted of sixteen patients previously selected and randomly assigned to group one (rhBMP-2) or group two (iliac crest bone graft). Results. DDPSC could be isolated and characterized as mesenchymal stem cells. Progressive alveolar bone union has occurred in all patients. Similarly to group two 75.4%, SD±4.0, p>0.999, but statistically different from group one (59.6%, SD±9.9, p=0.001), completion of the defect with 75.6% (SD±4.8) of bone filling was detected 6 months postoperatively. Dental eruption routinely occurred in 66.7% of patients. No complications were detected, in comparison to significant swelling in 37.5% of group one patients and significant donor site pain in 87.5% of group two. Conclusion. For this selected group of patients, DDPSC therapy resulted in satisfactory bone healing with excellent feasibility and safety, which adds significantly to the prospect of stem cell use in clinical settings. Clinical Question/Level of Evidence. Therapeutic, II. This trial is registered with https://clinicaltrials.gov/ct2/show/NCT01932164?term=NCT01932164&rank=1.